Primate Craniofacial Function and Biology - Vinyard, Chris (Springer, 2017)
Primates have unusual heads among mammals. Their big brains, relatively short faces and forward-facing eyes are part of a unique combination of traits that have captured the interest of biological anthropologists for decades. Describing the patterns of primate craniofacial evolution as well as sorting out the functional consequences of this evolutionary history has been fundamental in developing our current understanding of primates. Primate Craniofacial Function and Biology surveys current research on primate heads emphasizing the recent progress and diversity of functional studies into primate and mammalian craniofacial form. Much of the work included in this volume was inspired by William L. Hylander and his life-long contribution to research on primate craniofacial form and function.